The performance of children and adolescents with low vision on the Pediatric Balance Scale - Agda Cristina de Sousa Santos; Hanne Alves Bakke; Ilana Santos de Oliveira; Silvia Warnick Sarinho (Desafio Singular, 2018)
The aim of this study was to investigate the performance of children and adolescents with low vision on the Pediatric Balance Scale (PBS), in different age groups. The PBS was administered to 41 subjects, aged 5 to 14 years, with low vision and no other associated disorders. The Spearman correlation coefﬁcient was used for correlation between age and the score achieved on the scale. There was a correlation of 0.52 between the score obtained on the PBS and the age. The variation of score was greater in children between 5 to 7 years and minimal in older age groups. The maximum score was obtained by all the subjects on six items of the scale. The PBS score had significant correlation with age up to a point, reaching ceiling effect on various items. It showed to be an easy application screening tool in children and adolescents with low vision, being more suitable for children 5-7 years old.